Effect of application of organic materials on growth and foliar nutrient contents of black pepper (Piper nigrum L.) - WAHID, C SIVA KUMAR, P A (Journal of Spices and Aromatic Crops, 1994)
The effect of soil application of organic materials (leaves of Erythrina indica, Garuga pinnata, Grevilea robusta, Piper nigrum and Coffea arabica) on growth and nutrition of black pepper vines (Piper nigrum) was studied in pot culture experiments. A substantial increase in growth and biomass production was noticed in vines treated with organic materials as compared to control. However, application of leaves of C. arabica and P. nigrum at higher rates suppressed growth of vines probably due to allelopathic effects of the decay products of these materials in the soil. The rates of decomposition ofleafmaterials in the soil varied considerably. Leaves of C. arabica and G. robusta were the most persistent while that of G. pinnata was least resistant to decomposition.